Explanatory model of the relationship between study habits, sex and provenance of the school in high school graduands from low socioeconomic status - Bazán Guzmán, Jorge (2001)
Through a comparative correlacional study, the relationship was evaluated amog study habits by sex and origin of the school. By means of an analysis log lineal, six explanatory models of the relationship were evaluated, using the rates of advantages for the interpretations of the select pattern. The participants are students of 5to of secondary of two equivalent mixed schools, of Lima (73) and of Country: Chimbote (61), of socioeconomic level under between 16 and 18 years. The used instrument is the Cuestionary Maddox adapted conceptually by Bazán and Aparicio (1993). It was found that the study habits of the students are moderate, that the habits averages of the provincial and the women they are better that their Limean couples (t=5.34, p=0.0001) and males (t=3.59, p=0.0001)respectivamente. The best selected model is that that she affirms that as much the origen as the sex explain the types of study habits independently (G2= p=0.5748). This explanation is bigger in the case of the origin that the sexo For a Limean student with appropiate habits there are four of country with the same level of habits, and for each male student with appropiate habits there are three students women with the same level of habits.